Molecular Mechanisms and Risk Factors for the Pathogenesis of Hydrocephalus - Li, Jingwen; Zhang, Xinjie; Guo, Jian; Yu, Chen; Yang, Jun (Frontiers in Genetics, 2022)
Hydrocephalus is a neurological condition due to the aberrant circulation and/or obstruction of cerebrospinal fluid (CSF) flow with consequent enlargement of cerebral ventricular cavities. However, it is noticed that a lot of patients may still go through symptomatic progression despite standard shunting procedures, suggesting that hydrocephalus is far more complicated than a simple CSF circulative/obstructive disorder. Growing evidence indicates that genetic factors play a fundamental role in the pathogenesis of some hydrocephalus. Although the genetic research of hydrocephalus in humans is limited, many genetic loci of hydrocephalus have been defined in animal models. In general, the molecular abnormalities involved in the pathogenesis of hydrocephalus include brain development and ependymal cell dysfunction, apoptosis, inflammation, free radical generation, blood flow, and cerebral metabolism. Moreover, recent studies have indicated that the molecular abnormalities relevant to aberrant cerebral glymphatic drainage turn into an attractive subject in the CSF circulation disorder. Furthermore, the prevalent risk factors could facilitate the development of hydrocephalus. In this review, we elicited some possible fundamental molecular mechanisms and facilitating risk factors involved in the pathogenesis of hydrocephalus, and aimed to widen the diagnosis and therapeutic strategies for hydrocephalus management. Such knowledge could be used to improve patient care in different ways, such as early precise diagnosis and effective therapeutic regimens.